Forward-backward translation and cross-cultural validation of the Center for Epidemiologic Studies Depression scale among Tigrigna-speaking Eritrean refugees. Issue 2 (30th May 2019) - Mogos, Mulubrhan F.; Beckstead, Jason W.; Evans, Mary E.; Kip, Kevin E.; Boothroyd, Roger A.
Abstract : Purpose: The Center for Epidemiologic Studies Depression (CES-D) scale is a widely used instrument for studying depression in the general population. It has been translated into several languages. Cross-cultural relevance of the construct of depression and cultural equivalence of the CES-D items used to measure it are crucial for international research on depression. Given the increasing number of refugees from Eritrea entering the USA and Europe, there is a need among health care researchers and providers for an instrument to assess depressive symptoms in the native language of this vulnerable population. The paper aims to discuss these issues. Design/methodology/approach: The study employed forward–backward translation and assessed the CES-D scale for cross-cultural research and depression screening among Tigrigna-speaking Eritrean refugees. Forward–backward translation, cognitive interview and semantic analysis were conducted to ensure equivalence of comprehension of the items and instructions between Tigrigna- and English-speaking samples. Multi-group confirmatory factor analysis was used to assess the measurement invariance of the translated version. Findings: Translation efforts were successful as reflected by the results of semantic analysis and pilot testing. Evidence supporting the measurement invariance of data collected using the Tigrigna version of the CES-D was obtained from a sample of 253 Eritrean refugees in the USA. Practical implications: The findings of this study provide support for reliability and validity of data collected using the Tigrigna version of the CES-D scale. This important tool for assessing depression symptoms among Eritrean refugees is now available for health care providers and researchers working with this vulnerable population. Originality/value: This work is an original work of the authors and it has not been published previously.